2013
DOI: 10.1590/s0004-28032013000200032
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease in Menopausal Women

Abstract: -Context -Nonalcoholic Fatty Liver Disease (NAFLD) is common in postmenopausal women. It is associated with metabolic syndrome. However, the influence of hormone replacement therapy in NAFLD development in these women needs to be investigated. This study aimed to describe the clinical characteristics of NAFLD in postmenopausal women, and the relationship between hormone replacement therapy and this disease. (79/198) without hormone replacement therapy. Gamma-glutamyl transpeptidase (P = 0.001), alanine transam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 23 publications
4
38
0
1
Order By: Relevance
“…The alleviation of hepatic steatosis is associated with the activations of PPAR-a and AMPK, which induce lipolysis (Hwang et al 2011;Guo et al 2011;Seymour et al 2011). Postmenopausal women and estrogen-deficient female animals easily develop hepatic steatosis with diets in high fat and cholesterol (Kamada et al 2011;Florentino et al 2013). OVX was shown to be associated with decreased hepatic expression of catabolic gene expression including CPT-1 by 53 % and b-hydroxyacyl-CoA dehydrogenase by 27 %, and increased hepatic anabolic gene expression of sterol regulatory element-binding protein-1c by 106 %, ACC by 72 % and stearoyl CoA desaturase-1 by 109 % (Kamada et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alleviation of hepatic steatosis is associated with the activations of PPAR-a and AMPK, which induce lipolysis (Hwang et al 2011;Guo et al 2011;Seymour et al 2011). Postmenopausal women and estrogen-deficient female animals easily develop hepatic steatosis with diets in high fat and cholesterol (Kamada et al 2011;Florentino et al 2013). OVX was shown to be associated with decreased hepatic expression of catabolic gene expression including CPT-1 by 53 % and b-hydroxyacyl-CoA dehydrogenase by 27 %, and increased hepatic anabolic gene expression of sterol regulatory element-binding protein-1c by 106 %, ACC by 72 % and stearoyl CoA desaturase-1 by 109 % (Kamada et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in an OVX SpragueDawley rat model, 17b-estradiol treatment decreased fatty acid synthesis in a hepatic zone 3-specific manner through increasing the phosphorylation of acetyl coenzyme-A carboxylase via an estrogen receptor-a-mediated pathway (Zhang et al 2013). Menopausal women have been shown to exhibit hepatic steatosis which is ameliorated by estrogen replacement therapy, although the results are inconsistent (Florentino et al 2013;McKenzie et al 2006). Thus, the activation of estrogen receptors in the liver may prevent hepatic steatosis by increasing b-oxidation of fatty acids and decreasing lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that menopause is associated with NAFLD [15][16][17]. The increase in prevalence of NAFLD following menopause implies that estrogen may have protective effects against NAFLD and/or its associated risk factors [17,19,27]. The NHANES study also demonstrated that the prevalence of NAFLD is higher in postmenopausal women compared with premenopausal women (odds ratio 2.05, 95% CI: 1.43-2.94) [15].…”
Section: Commentsmentioning
confidence: 99%
“…Furthermore, it has been reported that NAFLD is twice as common in postmenopausal women compared to premenopausal women [15]. Additionally, anti-oestrogens double the risk of NAFLD and use of hormone replacement therapy is negatively association with NAFLD [16][17][18][19], which may be interpreted as indirect evidence for the protective role of endogenous oestrogens against NAFLD. The 2011 Stages of Reproductive Aging Workshop (STRAW+10) report was based on a consensus conference of expert committees in the field of female reproductive aging.…”
Section: Introductionmentioning
confidence: 99%
“…Posztmenopauzában levő nőknél a testösszetétel és a lipid profil megváltozása, az ektópiás zsírlerakódás, valamint az emelkedett glükóz-, inzulin-, és leptin szint elősegítik a nem alkoholos zsírmáj (NAFLD) kialakulást. A NAFLD a népesség széles körét érintő betegség, előfordulása igen gyakori posztmenopauzális állapotban [84,85]. Az ösztrogénhiány következtében fellépő metabolikus elváltozások fokozzák a kardiovaszkuláris rizikót.…”
Section: Az öSztrogénhiány Metabolikus Változások éS a Kardiovaszkulunclassified